The Historical Roots of Corporate Social Responsibility in Indonesia: The Institutionalization of Social Welfare in the Mangkunegaran Sugar Industry, 1861–1940 - Wasino; William Bradley Horton; Hartatik Endah Sri; Witasari Nina; Aricindy Argitha; Scientia Inu Kirana Enwa Siwi; Sina Fortuna Devi Putri (istory Department, Faculty of Social Sciences, Universitas Negeri Semarang in collaboration with Masyarakat Sejarawan Indonesia (Indonesian Historical Society), 2026)
Abstract: Corporate Social Responsibility (CSR) is often understood as a modern normative concept that was only adopted in Indonesia in the post-2000 period. This study challenges that assumption by tracing the historical roots of CSR-like practices through an examination of social welfare initiatives in the Mangkunegaran sugar industry between 1861 and 1940. Employing historical research methods, this study analyzes how welfare initiatives at the Colomadu and Tasikmadu sugar factories evolved from ad hoc responses into an institutionalized system. The findings demonstrate that the Mangkunegaran sugar enterprises implemented practices that can be categorized as “Proto-CSR,” driven by a Dual Logic: economic rationality aimed at maintaining labor productivity, and a moral-cultural obligation of the ruler rooted in Mangkunegaran leadership ethics to protect and care for the populace (kawula). This institutionalization culminated in the establishment of the Bevolkingfondsen (Population Fund), a formal financing mechanism that supported healthcare services, housing improvements, and public sanitation. This study concludes that the Mangkunegaran welfare practices conceptually preceded the modern notion of Creating Shared Value (CSV). These findings contribute to the theoretical discourse on CSR by demonstrating that corporate social responsibility in Indonesia has deep indigenous and historical roots, rather than being merely an adoption of contemporary global management standards. Abstrak: Tanggung Jawab Sosial Perusahaan (CSR) kerap dipahami sebagai konsep normatif modern yang baru diadopsi di Indonesia pada era pasca-2000. Penelitian ini menantang asumsi tersebut dengan menelusuri akar historis praktik tanggung jawab sosial melalui studi kasus industri gula Mangkunegaran pada periode 1861–1940. Dengan menggunakan metode sejarah, penelitian ini menganalisis transformasi inisiatif kesejahteraan sosial di pabrik gula Colomadu dan Tasikmadu dari respons situasional menjadi sistem yang terlembaga. Temuan penelitian menunjukkan bahwa industri gula Mangkunegaran telah menjalankan praktik yang dapat dikategorikan sebagai “Proto-CSR”, yang digerakkan oleh Logika Ganda (Dual Logic): rasionalitas ekonomi untuk menjaga keberlanjutan produktivitas tenaga kerja, serta kewajiban moral-budaya penguasa berakar pada etos kepemimpinan Mangkunegaran—untuk mengayomi rakyat (kawula). Pelembagaan praktik ini mencapai bentuk formal melalui pembentukan Bevolkingfondsen (Dana Penduduk), sebuah mekanisme pendanaan yang menopang layanan kesehatan, perbaikan permukiman, dan sanitasi publik. Penelitian ini menyimpulkan bahwa praktik kesejahteraan sosial Mangkunegaran secara konseptual mendahului gagasan Creating Shared Value (CSV). Temuan ini berkontribusi pada pengayaan wacana teoretis dengan menunjukkan bahwa CSR di Indonesia memiliki akar historis dan kultural yang kuat, serta tidak semata-mata merupakan adopsi dari standar global modern.